Effect of organizational leadership behavior and empowerment on job satisfaction - Fauzi Hussin, Muhammad Naveed Jabbar, (Opción, 2019)
This research aims to determine the effect of organizational leadership behavior and empowerment on job satisfaction of the university teachers. The current study was designed by using the quantitative approach for which the survey research method was used to conduct it. The findings of the study show that organizational leadership behavior and empowerment have a significant effect on job satisfaction among public university teachers in Punjab, Pakistan. In conclusion, the seminar and workshops should be conducted in different areas of the country for the awareness of organization leadership strategies and job satisfaction.